2019
DOI: 10.1097/md.0000000000014298
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of high b-value (2000 s/mm2) DWI for thyroid micronodules

Abstract: The aim of the study was to assess the diagnostic value of high b-value (2000 s/mm2) diffusion-weighted imaging (DWI) in differentiating malignant from benign thyroid micronodules.Consecutive patients with thyroid micronodules scheduled for Ultrasound (US)-guided fine-needle aspiration biopsy (FNAB) or surgery were underwent high b-value DWI with 3 b-values: 0, 800, and 2000 s/mm2. Signal intensity ratios (SIRs) of thyroid micronodules to adjacent normal thyroid tissue on DWI were measured as SIRb0, SIRb800 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Leila et al reported that static MRI measurements like signal intensity and heterogeneity were not useful in distinguishing between benign and malignant lesions (31). However, Wang et al showed that DWI SIR was lower in benign nodules than in malignant ones (32), which corroborated with our ndings. In our study, we found that DWI SIR was another independent predictor of malignant nodules, with malignant nodules showing a higher DWI SIR .…”
Section: Comparison Of the Diagnostic Performance With Acr-tiradssupporting
confidence: 90%
“…Leila et al reported that static MRI measurements like signal intensity and heterogeneity were not useful in distinguishing between benign and malignant lesions (31). However, Wang et al showed that DWI SIR was lower in benign nodules than in malignant ones (32), which corroborated with our ndings. In our study, we found that DWI SIR was another independent predictor of malignant nodules, with malignant nodules showing a higher DWI SIR .…”
Section: Comparison Of the Diagnostic Performance With Acr-tiradssupporting
confidence: 90%
“…Quality of the machine could affect the result of examination [2,3]. In the recent literature, many authors have been deeply studying and analyzing the value of MRI in evaluating malignancy of thyroid [4][5][6]. With the advancement of high field magnetic resonance machines, especially the recent advanced pulse sequences, the oncology diagnosis of thyroid on MRI turns out to be a lot simpler.…”
Section: Introductionmentioning
confidence: 99%
“…According to Abdel Razek et al [14], DWI combined with ADC maps can help identify metastatic non-necrotic lymph nodes and provide microscopic information about lymph node status. Recently, Wang et al [15] concluded that a high b value (2000 s/mm 2 ) has high accuracy for the differential diagnosis of benign and malignant thyroid micronodules.…”
Section: Discussionmentioning
confidence: 99%